Apical Cyanide Ligand Substitution in Heterometallic Clusters [Re3Mo3Q8(CN)6]n– (Q = S, Se). Issue 22 (5th June 2019) - Muravieva, Viktoria K.; Gayfulin, Yakov M.; Lappi, Tatiana I.; Dorcet, Vincent; Sukhikh, Taisiya S.; Lemoine, Pierric; Ryzhikov, Maxim R.; Mironov, Yuri V.; Cordier, Stéphane; Naumov, Nikolay G.
Abstract : A number of transition metal cluster compounds can be obtained only in the melt of inorganic cyanides and, therefore, contain terminal cyanide ligands. Substitution of these ligands, which is often necessary to change the physicochemical properties of the clusters, is an urgent problem because of their low reactivity in substitution reactions. In this work, a synthetic approach has been developed for the substitution of CN‐ligands in the heterometallic cluster anions [Re3 Mo3 Q8 (CN)6 ] n– (Q = S, n = 6; Q = Se, n = 5) by the 4‐ tert ‐butylpyridine (TBP) molecules. Two new compounds, namely [Re3 Mo3 S8 (TBP)6 ] (1 ) and [Re3 Mo3 Se8 (TBP)6 ] (2 ), were obtained with high yields and crystallized under solvothermal conditions. It has been shown that compounds1 and2 are based on the paramagnetic cluster cores Re3 Mo3 Q8 0 containing 23 cluster valence electrons (CVE). The geometry of the new compounds has been investigated using X‐ray structural analysis. The electronic structure has been analyzed using the DFT calculations showing large distortion of M6 cluster core. Abstract : Reaction of [Re3 Mo3 Q8 (CN)6 ] n – (Q = S, n = 6; Q = Se, n = 5) complexes with the 4‐ tert ‐butylpyridine (TBP) leads to compete substitution of coordinated cyano ligands and formation of two new heterometallic complexes [Re3 Mo3 Q8 (TBP)6 ] (Q = S, Se) obtained with high yields. DFT calculations show a large distortion of the M6 metal cores in the complexes.